Konsep Pendidikan Islam dengan Paradigma Humanis - Subaidi, Subaidi (Nadwa, 2016)
Education is a rehumanisme, that was oriented to form individuals who able to understand the reality itself and the surrounding communities. The aim of education is to create significant social change in the life of mankind. One of the contents of the national education goals is to appreciate the reality of humanity and the potential that owned learners (human). Islam in its victorius was a center of the study of various discipline. It was proved by the emergence of Muslim scientists. But over time, the Islamic intellectualism began to decline along with cultural understanding and taqlid, whereas al-Qur`an have many signaled to examines all disciplines, not limited to the religious sciences. It can be seen from the verses of al-Qur`an that ordered to examine the verses kauniyah. Thus Islamic comprehensive assessment is a paradigm of Humanist Islamic Education or in other words, humanize human accordance with the primary task of man as a khalifah on earth.Abstrak:Pendidikan merupakan pemanusiaan kembali manusia (humanisasi) yang berorientasi pada bentuknya individu yang mampu memahami realitas dirinya dan masyarakat sekitarnya serta bertujuan untuk menciptakan perubahan sosial secara signifikan dalam kehidupan umat manusia. Salah satu isi dari tujuan pendidikan nasional adalah menghargai realitas kemanusiaan dan berbagai potensi yang dimilki peserta didik (manusia). Islam pada masa kejayaannya menjadi pusat kajian berbagai disiplin ilmu, hal ini terbukti dengan bermunculannya para ilmuwan muslim. Tetapi seiring dengan berjalannya waktu, intelektualisme Islam itu mulai redup seiring dengan pemahaman dan budaya taqlid, padahal al-Qur`an banyak memberikan isyarat agar mengkaji semua disiplin ilmu, tidak terbatas ilmu-ilmu agama saja. Hal ini bisa dilihat dari ayat-ayat al-Qur`an yang memerintahkan untuk mengkaji ayat-ayat kauniyah. Dengan demikian Pengkajian Islam secara komprehenshif baik ilmu agama maupun umum adalah sebagai Paradigma Pendidikan Islam Humanis atau dengan kata lain memanusiakan manusia sesuai dengan tugas utama manusia sebagai khalifah di muka bumi.